Upaya Meningkatkan Hasil Belajar Kognitif Matematika Kelas II A SDN Mlajah 2 Melalui Penggunaan Media Pembelajaran Tangga Pintar - Alika Ramadhanti; Firdausi Oktaviani; Agung Setyawan (Journal on Education, 2023)
This study aims to improve mathematics learning outcomes by applying the mathematics learning media of the unit weight ladder in class II students of SDN Mlajah 02. The data collection techniques used in this study were interviews, tests, and documentation. The results showed that in the pre-cycle activities there were still many students who had low pretest results, where class II A only got an average of 63.5 with a completeness percentage of only 44%. Then after being given the action and carrying out the test in cycle 1, class II A, namely getting an average of 71.6 with a completeness percentage of only 80%, this shows that there is an increase in learning outcomes from before being given action until after cycle 1. Then in cycle 2 class II A gets an average of 76.6 with a completeness percentage of only 88%, that is, with 40 students completing and 5 students not completing. The results of this study are very important to determine the effect of the learning media that research uses. The results of the study showed that there was an increase in mathematics learning outcomes on weight unit material using smart ladder media in class IIA SDN Mlajah 02 Bangkalan students.